Administrative and legal limitations of the investment and construction process in closed areas in Poland - Ziniewicz, Monika Anna (Studia Iuridica Toruniensia, 2021)
The investment and construction process is a whole of complex activities aimed at the development of space with construction objects. This process is related to the constitutional principle of building freedom. This freedom means that the investor can act freely. However, the question remains whether the investor can freely undertake investment activities in each area. The article analyzes the implementation of the investment and construction process in closed areas reserved for the purposes of national defense and security. It has been shown that in these areas the legislator introduces a separate legal regime for its implementation in the form of administrative and legal restrictions. For this purpose, the provisions contained in the Act of March 27, 2003 on spatial planning and development, the Act of August 21, 1997 on real estate management, the Act of July 7, 1994, Construction Law, the Act of May 17, 1989 Geodetic and Cartographic Law and the Act of 5 August 2012 on the protection of classified information were analyzed.